Si nanorod arrays modified with metal–organic segments as anodes in lithium ion batteries. Issue 85 (22nd November 2017) - Yu, Yingjian; Yue, Chuang; Han, Yingzi; Zhang, Chuanhui; Zheng, Mingsen; Xu, Binbin; Lin, Shuichao; Li, Jing; Kang, Junyong
Abstract : Metal–organic segments (MOSs) were synthesized to composite with Si nanorod (NR) arrays as electrodes in lithium ion batteries (LIBs). Abstract : Metal–organic segments (MOSs) have been controllably synthesized to composite with Si nanorod (NR) arrays as electrodes in lithium ion batteries (LIBs). These kinds of MOSs are suggested to be derived from solution species such as [Zn(C4 H6 N2 )Ac] +, [Zn(C4 H6 N2 )2 Ac] + and [Zn(C3 H4 N2 )(C4 H6 N2 )Ac] + as detected by electrospray ionization time-of-flight mass spectrometry (ESI-TOF-MS). It is found that solution concentration and growth time have significant effects on the MOS coating around Si NRs. The uniform coating of MOSs around Si NRs has been successfully produced at relatively low solution concentrations or for shorter growth time, which was proved to be helpful to enhance the capacity of the composite electrode up to ∼1.1 mA h cm −2 at a current density of 10 μA cm −2 and ∼0.5 mA h cm −2 on increasing the current density to 50 μA cm −2 . Furthermore, at an even higher current density of 200 μA cm −2 ( vs. initial 10 μA cm −2 ) the composite electrodes still can maintain more than 50% of the initial capacities. While, given a higher solution concentration or longer reaction time, large ZIF-61 crystals, a kind of metal–organic framework (MOF), would form on the top of Si NRs. Unlike MOSs, large ZIF-61 crystals fail to cover the Si NR homogeneously, and consequently the capacities of ZIF-61/Si NR composite electrodes are much lower than those of MOS/Si NR electrodes. This work not only demonstrates a simple method for Si surface modification to enhance its corresponding electrochemical performance, but also provides a potential general strategy for the coating of different surfaces by the cross-linking of metal nodes and organic ligands.